Reflections of the Political Organization of the Bosniaks of Bosnia and Herzegovina on the Bosniaks of Sanjak and the Diaspora 1990-1991. - Admir Lisica (Historijski pogledi, 2023)
The political organization of Bosniaks dates back to the beginning of the twentieth century, more precisely in 1906, when a group of Bosniak intellectuals formed the first political party called the Muslim People's Organization. As a result of the global political upheavals that affected most of Europe, certain decisions of international officials (primarily the Congress of Berlin in 1878) from the end of the nineteenth century complicated the position of Bosnia and Herzegovina, as well as the Bosniaks. Realizing that through political activism they can defend their own interests in the newly emerging constellation of relations, Bosniak dignitaries led by Ali-beg Firdus and other dignitaries began a demanding political struggle. The scope of Bosniak politics at that time was extremely limited, as were the political organizations and representatives of Bosniaks in the years after, in contrast to the end of the twentieth century when politically organized Bosniaks managed to restore their national name Bosniak, the Bosnian language, but also democratically fight for an independent Bosnia and Herzegovina. Namely, during the twentieth century, the political development of Bosniaks can be traced, which at the beginning of the nineties experienced a kind of culmination in the context of the achieved results. In that process, two years can be considered extremely important in the context of the political organization of Bosniaks in the period of the beginning of the dissolution of Yugoslavia. and those are definitely 1990 and 1991. The first year (1990) is important because of the officialization of political pluralism in the country at that time, while during 1991 processes took place that would not only change the everyday life of Bosniaks, but also the whole of Yugoslavia. The Bosniaks saw the introduction of democratic principles into daily life in Yugoslavia as an opportunity for renewed political organization, which was imposed as a logical sequence of the circumstances of a nation in the post-communist period. The formation of the first Bosniak political party during the nineties - the Party of Democratic Action - SDA, started the Bosniak struggle for equality, but also the preservation of the position of Bosnia and Herzegovina within Yugoslavia, and later as an independent state. The aim of the paper is to present the way of the initial political organization of Bosniaks due to the new political reality in Yugoslavia, with a focus on Bosnia and Herzegovina and Sandžak, with an overview of organizing throughout the Bosniak diaspora. In historiography, the role of the Bosniak diaspora in the context of the original political organization during the nineties has often been unfairly neglected. The Bosniak diaspora carefully followed all events in Yugoslavia, and tried to be a part of them in all available ways. The beginning of political organizing among Bosniaks in Bosnia and Herzegovina and Sandžak was followed with great attention, and Bosniak political activists from Bosnia and Herzegovina and Sanjak often went together on tours throughout the diaspora, with the aim of including Bosniaks outside their homeland in important processes that then took place in Yugoslavia. The political struggle of Bosniaks in Sanjak, about which the Bosnian public knows very little, took place almost parallel to the one in Bosnia and Herzegovina. The political representatives of Bosniaks from Sanjak experienced various forms of segregation by the Great Serbian regime from Belgrade, as evidenced by various official documents and other sources, which were used in the preparation of this work. According to the above, there is a need to research such a topic, which has the task of encouraging other authors to investigate this period in more detail. In the context of the methodology of the work, it is worth noting that the work will primarily contain the thematic and chronological methods, with the use of other methods for which the need arises, for the purpose of improving the quality of the work. The paper before you is not the final letter on the mentioned topic, but an attempt to answer some important and unavoidable questions from the beginning of the nineties of the last century, in the context of the political history of Bosniaks.